Weight cycling and relative energy deficiency in sport syndrome in an elite female muaythai athlete: a case study - Bulínová, Viktorie; Wagner, Adam; Kumstát, Michal (Frontiers in Sports and Active Living, 2025)
IntroductionWeight cycling—defined as repeated, chronic, and often extreme weight loss is a widespread practice in combat sports. However, it may lead to symptoms related to Relative Energy Deficiency in Sport (REDs). This case study investigates the impact of a five-week fight camp on the health and performance of an elite female Muaythai athlete, with a particular focus on metabolic and physiological adaptations.MethodsA 23-year-old professional Muaythai fighter was monitored over a seven-week period, encompassing a control phase, a five-week fight camp, the fight week, and post-fight recovery. Measurements included body composition, resting metabolic rate (RMR), blood biomarkers, and performance in a cycling power test. Dietary intake and training load were also tracked.ResultsThe athlete's RMR decreased by 253 kilocalories per day. Blood markers indicated increased creatinine and urea levels, along with unfavorable changes in lipid profile. Maximum cycling power output decreased by 27%. Despite a significant energy deficit, fat-free mass loss was limited to 0.6. These findings suggest metabolic adaptations, signs of renal strain, and symptoms of REDs.ConclusionWeight cycling induced physiological and metabolic adaptations consistent with REDs, negatively affecting health and performance. The results highlight the importance for individualized and evidence-based weight management strategies to mitigate negative health outcomes and enhance athletic performance in combat sports.